Play Therapy for Improving Interaction and Communication in Autism: Systematic Review - Karina Gading Yustesari; Nur Azizah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Early childhood children use a play-based approach to learning, which includes elements of communication and interaction with the environment. Unfortunately, autistic children experience problems interacting and require special treatment. This research is a literature review and uses descriptive analysis techniques. Data was taken based on journals published in 2013–2023. The aim of writing this article is to identify play therapy methods applied by teachers and therapists to improve the development of interaction and communication in autistic children. The research results show that there are eight play therapy types that are applied to young autistic children. Play therapy consists of associative games, games with squishy media, Child-Centered Play Therapy (CCPT), Short Play and Communication Evaluation (SPCE), games with flashcard media, group play, and symbolic games.